ERdj3B-Mediated Quality Control Maintains Anther Development at High Temperatures. Issue 4 (24th January 2020) - Yamamoto, Masaya; Uji, Shuhei; Sugiyama, Tomoyuki; Sakamoto, Tomoaki; Kimura, Seisuke; Endo, Toshiya; Nishikawa, Shuh-ichi
Abstract : ER quality control mediated by ERdj3B is important for anther development at high temperature in Arabidopsis. Abstract: Pollen development is highly sensitive to heat stress, which impairs cellular proteostasis by causing misfolded proteins to accumulate. Therefore, each cellular compartment possesses a dedicated protein quality control system. An elaborate quality control system involving molecular chaperones, including immunoglobulin-binding protein (BiP), heat shock protein70, and regulatory J domain-containing cochaperones (J proteins), allows the endoplasmic reticulum (ER) to withstand a large influx of proteins. Here, we found that Arabidopsis ( Arabidopsis thaliana ) mutants of ER-localized DnaJ family 3B (ERdj3B), one of three ER-resident J proteins involved in ER quality control, produced few seeds at high temperatures (29°C) due to defects in anther development. This temperature-sensitive fertility defect is specific to the defective interactions of BiP with ERdj3B but not with the other two J proteins, indicating functional differences between ERdj3B and the other J proteins. RNA sequencing analysis revealed that heat stress affects pollen development in both wild-type and mutant buds, but the erdj3b mutant is more susceptible, possibly due to defects in ER quality control. Our results highlight the importance of a specific ER quality control factor, ERdj3B, for plant reproduction, particularly anther development, at high temperatures.